The Non-Steroidal Mineralocorticoid Receptor Antagonist KBP-5074 Limits Albuminuria and has Improved Therapeutic Index Compared With Eplerenone in a Rat Model With Mineralocorticoid-Induced Renal Injury - Jaisser, Frédéric; Tan, Xiaojuan; Chi, Shuangshuang; Liu, Jinrong; Wang, Ping; Bush, Mark; Benn, Vincent; Yang, Y. Fred; Zhang, Jay (Frontiers in Pharmacology, 2021)
The therapeutic indices (TIs) and efficacy of the non-steroidal mineralocorticoid receptor antagonist (MRA) KBP-5074 and steroidal MRA eplerenone were evaluated in a uninephrectomized Sprague-Dawley (SD) rat model of aldosterone-mediated renal disease. Rats were placed on a high-salt diet and received aldosterone by osmotic mini-pump infusion over the course of 27 days. The urinary albumin-to-creatinine ratio (UACR) was evaluated after 7, 14, and 26 days of treatment. Serum K+ was evaluated after 14 and 27 days of treatment. Urinary Na+, urinary K+, and urinary Na+/K+ ratio were evaluated after 7, 14, and 26 days of treatment. The TI was calculated for each drug as the ratio of the concentration of drug producing 50% of maximum effect (EC50) for increasing serum K+ to the EC50 for lowering UACR. The TIs were 24.5 for KBP-5074 and 0.620 for eplerenone, resulting in a 39-fold improved TI for KBP-5074 compared with eplerenone. Aldosterone treatment increased UACR, decreased serum K+, and decreased urinary Na+ relative to sham-operated controls that did not receive aldosterone infusion, validating the aldosterone/salt renal injury model. KBP-5074 prevented the increase in UACR at 0.5, 1.5, and 5 mg/kg BID while eplerenone did so only at the two highest doses of 50 and 450 mg/kg BID. Both KBP-5074 and eplerenone blunted the reduction in serum K+ seen in the aldosterone treatment group, with significant increases in serum K+ at the high doses only (5 mg/kg and 450 mg/kg BID, respectively). Additionally, urinary Na+ and Na+/K+ ratio significantly increased at the middle and high doses of KBP-5074, but only at the highest dose of eplerenone. These results showed increased TI and efficacy for KBP-5074 compared with eplerenone over a wider therapeutic window.